Analisis Komprehensif Metode Manajemen Penyimpanan dalam Sistem Operasi Cloud - Hendra Parsaulian; Yudi Fermana; Elkin Rilvani (International Forum of Researchers and Lecturers, 2025)
The main focus of this research is to examine data storage efficiency methods, algorithm scheduling, and resource usage optimization techniques. This research uses literature study methods and simulation experiments to analyze system performance. The research results show that storage management methods based on deduplication and data compression have significant efficiency in reducing storage space requirements. The implications of this research include improving cloud system performance and reducing operational costs.